2011
DOI: 10.1152/ajpendo.00655.2010
|View full text |Cite
|
Sign up to set email alerts
|

Normal adaptations to exercise despite protection against oxidative stress

Abstract: It has been reported that supplementation with the antioxidant vitamins C and E prevents the adaptive increases in mitochondrial biogenesis and GLUT4 expression induced by endurance exercise. We reevaluated the effects of these antioxidants on the adaptive responses of rat skeletal muscle to swimming in a short-term study consisting of 9 days of vitamins C and E with exercise during the last 3 days and a longer-term study consisting of 8 wk of antioxidant vitamins with exercise during the last 3 wk. The rats i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
5
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 38 publications
9
114
5
4
Order By: Relevance
“…Interestingly, these two markers were normalised to LF levels upon ROS sequestering. This finding is in line with other reports showing that antioxidant supplementation suppresses exercise-induced mitochondrial biogenesis [43,44], suggesting a potential role of ROS in mitochondrial biogenesis, although not all studies support this conclusion [45].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, these two markers were normalised to LF levels upon ROS sequestering. This finding is in line with other reports showing that antioxidant supplementation suppresses exercise-induced mitochondrial biogenesis [43,44], suggesting a potential role of ROS in mitochondrial biogenesis, although not all studies support this conclusion [45].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the above findings, antioxidant supplementation in rodents has shown to have no effect on the expression of mitochondrial transcription factors (NRF1, NRF2 and Tfam) respiratory chain complexes (I-V), PGC-1α or upstream signalling activity (p38 MAPK and AMPK) following acute and chronic endurance exercise (Higashida et al, 2011;. Likewise, research within humans has shown that Vitamin C and E supplementation during a 12-week intense endurance training program had no influence on improvements in VO2max, power output at VO2max and power output at lactate threshold (Yfanti et al, 2010).…”
Section: Reactive Oxygen Speciescontrasting
confidence: 58%
“…Higashida et al studied the combined effect of vitamin C (750 mg / kg body weight / day) and vitamin E (150 mg kg body weight / day) supplemented on the adaptive responses training-induced muscle mitochondria and sensitivity to insulin in rats. Based on the results of this study, supplementation of vitamin C and E does not have an inhibitory effect or a promoter effect on the adaptive responses related to mitochondria and glucose metabolism in skeletal muscle to chronic exercise [23].…”
Section: Discussionmentioning
confidence: 75%